Rancang Bangun Portal Business Partner Berbasis Website Pada PT Properti Solusi Manajemen - Sari, Yunita; Reinardi, Aldo Davin (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Along with the increasingly rapid development of information technology, humans are trying tocreate equipment and systems that can simplify the data processing process and conveyinformation to produce a picture of data or information that is accurate and easy to understand.In carrying out relationships between Business to Business (B2B) or Business to Consusmer(B2C), companies need potential business partners who can work together to create efficienciesand opportunities. PT Properti Solusi Manajemen is a start-up company in the Property sectorwhich has a daily service provision sub-service with the product name Pinhome Service.Pinhome Service is here to make it easier to access cleaning and maintenance services forhomes, electronic equipment, vehicles and massage services. The partnership systemimplemented has made PT Properti Solusi Manajemen feel the need for informationtransparency between both parties. Therefore, PT Properti Solusi Management needs aninformation system that can be used to convey information regarding certain data to BusinessPartners in order to create a good relationship between PT Properti Solusi Management andBusiness Partners.